Pengembangan Modul Teknik Dasar Bola Basket Siswa Kelas VIII MTS - Ahmad Kurniadi; Ever Sovensi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
This study aims to develop a basic basketball technique module and to determine the quality of the module in terms of validity and practicality as well as having a potential effect. This research is a development research that refers to the development of the ADDIE model, namely Analysis (Analysis), Design (design or design), Development (Development), implementation (implementation or execution), and Evaluation (evaluation or feedback). The evaluation stage was not carried out due to the time in the study. The instruments used to measure the quality of the developed modules include validation sheets, practicality questionnaires with scores. The results showed that, 1) the module design seen from the aspect of validity was included in the very valid category with an average score of 4.5; 2) the quality of the module seen from the practical aspect is categorized as practical from the one to one test with an average score of 4.5 categorized as very practical and small groups with an average score of 4.5 categorized as very practical. In conclusion, the development of the basic basketball technique module has produced teaching material products that can be used by students in basketball learning Keywords: Basic Basketball Technique Module